Demazhabization of Islam, Divinity Economy and Narratives of Conflict of the Tablighi Followers in Samarinda East Kalimantan - Saipul Hamdi (Al-Albab, 2015)
Tablighi Jamaat is one of the world’s largest and most successful transnational Islamic movements with established branches built on the business of dakwa (proselytization) in approximately 180 countries. Tablighi’s strong commitment to a style of dakwa based on their reformist attitude and flexible practice of mazhab (schools of thought) through a process of ‘demazhabizasi’ (demahzhabization), has attracted interest from a range of people. Tablighi guarantees the freedom for its members to embrace their choice of mazhab, and prefers its proselytizers to follow the mazhab of the communities in which they preach in order to avoid religious debates. This article aims to understand the concept of ‘demazhabisasi’ that has developed in Tablihgi and the ways in which Tablighi members work to overcome and prevent conflict due to the different understandings of each mazhab. The material sacrifices Tablighi proselytizers make together with their reliance on and submission to God for their economy, has led this research to examine the concept of a ‘divine economy’ that has developed in Tablighi communities. Yet, behind Tablighi’s apparent success, conflict has emerged internally among Tablighi members, as well as externally among locals in the communities in which Tablighi proselytizers work. This research uses an ethnographic approach to explore narratives of conflict that have emerged as a result of Tablighi proselytizing practices in Samarinda, East Kalimantan.